2017
DOI: 10.1097/md.0000000000007198
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram prediction of postoperative surgical site infections in patients with perihilar cholangiocarcinoma

Abstract: Surgical site infection (SSI) is one of the major morbidities after radical resection for perihilar cholangiocarcinoma (PHCC). This study aimed to clarify the risk factors and construct a nomogram to predict SSIs in patients with PHCC.A total of 335 consecutive patients who underwent hepatectomy combined with hepaticojejunostomy between January 2013 and December 2015 were analyzed retrospectively. SSIs, including incisional (superficial and deep) and space/organ infection, were defined according to the Centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…We found that patients who underwent repeat hepatectomy were more likely to develop SSIs, consistent with previous studies[25-28]. One explanation for this finding is that, to ensure minimum trauma for patients, the original incision site was usually considered as the optimal operation approach for repeat hepatectomy.…”
Section: Discussionsupporting
confidence: 90%
“…We found that patients who underwent repeat hepatectomy were more likely to develop SSIs, consistent with previous studies[25-28]. One explanation for this finding is that, to ensure minimum trauma for patients, the original incision site was usually considered as the optimal operation approach for repeat hepatectomy.…”
Section: Discussionsupporting
confidence: 90%
“…15 The LC operation was performed in accordance with previously published literature. 4,8 ERCP operation was also performed according to the description of Li et al 16…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to identify the risk indicators for PPOI and determine optimal management strategies, a risk prediction model is urgently required. Of all the available models, a nomogram can provide a highly accurate, individualized evidence-based risk estimation[14,15]. Nomograms predicting survival of patients with unresectable or metastatic GC were well established[16].…”
Section: Introductionmentioning
confidence: 99%